Organizações internacionais de direitos humanos : a atuação da anistia internacional e da Human Rights Watch na ofensiva israelense Chumbo Fundido - Kurban, Thiago Müller (2017)
The present paper comparatively analyzes the reports prepared by international nongovernmental human rights organizations Amnesty International and HUMAN RIGTHS WATCH on the Israeli Operation Cast Lead. The Operation Cast Lead was a military offensive of great worldwide repercussion due to the significant number of Palestinian civilian deaths, the use of prohibited weapons and the controversy involving the Commission established by the United Nations Human Rights Council. The organizations selected for the work act in a large number of countries, have special consultative status with the UN Economic and Social Council, and have already received the Nobel Peace Prize. HRW's 2006 action in Lebanon allows to raise the hypothesis that such organizations can act influenced by external pressures and change their positions. The comparative analysis proposed here aims to verify the organizations' notes in order to test the hypothesis mentioned.